A Comparison between Two Force-Position Controllers with Gravity Compensation Simulated on a Humanoid Arm. (11th March 2013) - Muscolo, Giovanni Gerardo; Hashimoto, Kenji; Takanishi, Atsuo; Dario, Paolo
Abstract : The authors propose a comparison between two force-position controllers with gravity compensation simulated on the DEXTER bioinspired robotic arm. The two controllers are both constituted by an internal proportional-derivative (PD) closed-loop for the position control. The force control of the two systems is composed of an external proportional (P) closed-loop for one system (P system) and an external proportional-integrative (PI) closed-loop for the other system (PI system). The simulation tests performed with the two systems on a planar representation of the DEXTER, an eight-DOF bioinspired arm, showed that by varying the stiffness of the environment, with a correct setting of parameters, both systems ensure the achievement of the desired force regime and with great precision the desired position. The two controllers do not have large differences in performance when interacting with a lower stiffness environment. In case of an environment with greater rigidity, the PI system is more stable. The subsequent implementation of these control systems on the DEXTER robotic bioinspired arm gives guidance on the design and control optimisation of the arms of the humanoid robot named SABIAN.